Rnf32 is not essential for spermatogenesis and male fertility in mice - Kong, Hao; Yin, Yufeng; Zeng, Ni; Zhu, Yunfei; Cui, Yiqiang (PeerJ (San Francisco, CA), 2025)
Ring finger motifs are found in a variety of proteins with diverse functions, often involved in protein-DNA or protein-protein interactions. The -encoded protein contains two such motifs and is predominantly expressed in the testes and ovaries, suggesting that its expression may be regulated by elements within the promoter region. is active during spermatogenesis, mainly in spermatocytes and spermatids, indicating a potential role in sperm development. We established an knockout ( ) mouse model using CRISPR/Cas9 technology. Gene expression was analyzed reverse transcription quantitative polymerase chain reaction (RT-qPCR). Testicular and epididymal phenotypes were assessed through histological and immunofluorescence staining, and fertility and sperm motility were evaluated. Here, we successfully established an knockout mouse model using CRISPR/Cas9 technology. Surprisingly, male mice exhibited normal fertility, with no significant differences in testicular and epididymal histology, spermatogenesis, sperm count, or motility compared to mice. These findings suggest that may not be essential for male fertility in mice, and its potential functions warrant further investigation.